YUPQA PARDASI OʻTAOʻTKAZUVCHANLIK HARORATINING HOSILAVIY QIYMATLARI HAQIDA - Jalekeshov, A.S. (SCIENCE and SOCIETY, 2023)
A universal approach is proposed to study the influence of strain (pressure) on the temperature of Bose-Einstein condensation of intersite bipolarons within the extended Holstein model. It is shown that uniaxial strain (pressure) derivatives of the temperature of such a Bose-Einstein condensation strongly depend on the arrangement of ions in the lattice. In addition, their dependence on the level of doping was studied. In particular, derived values me be positive or negative. Theoretical and experimental results are discussed.